Women Creators in BoJack Horseman - Ortega Castillo, Jenny Paola (ACTIO Journal of technology in design, film arts and visual communication, 2023)
BoJack Horseman is one of the productions that treats mental illness as an experience in which numerous people who are diagnosed with mental disorders, to varying degrees, are recognized. In the series, most of the characters that are diagnosed are women, of the same genealogical line who share genetic inheritance and question the meaning of life, motherhood, abortion, success and happiness. What I suggest is that the animated women in the series had everything to do with the team of female directors, creators, filmmakers, producers and illustrators who were part of BoJack Horseman and who reoriented and modified their own diagnoses of mental illness, and took them to their creative works in a therapeutic and public process, which broadened the discussion about mental illness on the television screen and outside of it. From the field of cultural studies, this observation is about women who took agency over their own mental illness diagnoses.